Development and validation of an improved mechanical thorax for simulating cardiopulmonary resuscitation with adjustable chest stiffness and simulated blood flow. (May 2017) - Eichhorn, Stefan; Spindler, Johannes; Polski, Marcin; Mendoza, Alejandro; Schreiber, Ulrich; Heller, Michael; Deutsch, Marcus Andre; Braun, Christian; Lange, Rüdiger; Krane, Markus
Highlights: A thorax model with an circulatory circuit and variable chest stiffness for investigation CPR- techniques was developed. The model was validated using different experiments (cadavers, mechanical resuscitation devices, manual CPR). The model is representing the mechanical and circulatory properties during CPR. Abstract: Investigations of compressive frequency, duty cycle, or waveform during CPR are typically rooted in animal research or computer simulations. Our goal was to generate a mechanical model incorporating alternate stiffness settings and an integrated blood flow system, enabling defined, reproducible comparisons of CPR efficacy. Based on thoracic stiffness data measured in human cadavers, such a model was constructed using valve-controlled pneumatic pistons and an artificial heart. This model offers two realistic levels of chest elasticity, with a blood flow apparatus that reflects compressive depth and waveform changes. We conducted CPR at opposing levels of physiologic stiffness, using a LUCAS device, a motor-driven plunger, and a group of volunteers. In high-stiffness mode, blood flow generated by volunteers was significantly less after just 2 min of CPR, whereas flow generated by LUCAS device was superior by comparison. Optimal blood flow was obtained via motor-driven plunger, with trapezoidal waveform.